SAFRA Star Enterprise / Fatin Nadia Mohd Nasir... [et al.] - Mohd Nasir, Fatin Nadia; Mas'all, 'Ainun Dhabitah 'Aqilah; Lakman, Syaza Syasya; Nizam, Nur Arianna Iman; Jamalabdul Nazar, Raihana (2020)
Safra Star Enterprise is a company that is based on food & beverages . We will introduce our first product with an energy snack bar that will be named as JollyBar . This healthy snack will provide a nutritional facts to the consumers . We choose this healthy snack bar as our product because we could see their potential in the market as well as the other snack. Our jolly's Bar is named based on the meaning of the 'jolly' that is bring a meaning of happiness . This Jollybar contain a lot of nutrition level such as carbohydrate , protein and honey as natural sugar . The uniqueness of this scrumptious energy bar is we use honey as the source of our sweetener.We do not use sugarcane since it is too sweet and it is suitable to all range of ages. Moreover this energy bar are also suitable for those who are in a diet consumption tha(still want to have a sweet snack but it will not interfere their diet routine.